ANALISA PEREDAM PANAS GLASSWOOL PADA ALAT PEMBAKAR SAMPAH (INSINERATOR) PORTABEL 2 IN 1 - Dinda Estaniya Agustin; Wawan; Yadi Heryadi (Sekolah Tinggi Teknologi Wastukancana, 2022)
Abstract. Garbage is an environmental pollutant material that is always there at all times. To reduce environmental pollution, efforts are made to burn waste by using a tool in the form of an incinerator. An important aspect in designing an incinerator is to pay attention to the safety factor for the user when it is operated. The insulator in an incinerator has a very important role. In an effort to reduce the conduction of heat generated during combustion, the incinerator is coated with glass wool as an inner coating that is able to inhibit the heat that comes out when the tool is used. The method used in this study is to compare the temperature measurement of the inner wall of the SS400 Steel plate before being coated with glasswool, the measurement of the temperature of the combustion chamber of the incinerator and the measurement of the temperature of the outer wall of Zinc Galvalume. After the installation of glass wool in the incinerator, measurements were made in the combustion chamber, the results obtained reached ±700-800 oC. The results of this study indicate the use of glasswool can reduce the heat resistance that comes out of the SS400 steel plate wall but increases the temperature in the combustion chamber. The mass of waste and fuel can affect the combustion temperature that occurs. The output of organic waste is in the form of ash which can be used as fertilizer.